2016
DOI: 10.1098/rsos.150649
|View full text |Cite
|
Sign up to set email alerts
|

Is this scaling nonlinear?

Abstract: One of the most celebrated findings in complex systems in the last decade is that different indexes y (e.g. patents) scale nonlinearly with the population x of the cities in which they appear, i.e. y∼xβ,β≠1. More recently, the generality of this finding has been questioned in studies that used new databases and different definitions of city boundaries. In this paper, we investigate the existence of nonlinear scaling, using a probabilistic framework in which fluctuations are accounted for explicitly. In particu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
191
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(204 citation statements)
references
References 35 publications
9
191
1
Order By: Relevance
“…Empirical data from recent works [35,36] suggest that the residuals surrounding the scaling laws are log-normally distributed. The present model can explain such properties as a consequence of fluctuation of the interaction range of the citizen, given by particularities of the cities.…”
Section: Discussionmentioning
confidence: 99%
“…Empirical data from recent works [35,36] suggest that the residuals surrounding the scaling laws are log-normally distributed. The present model can explain such properties as a consequence of fluctuation of the interaction range of the citizen, given by particularities of the cities.…”
Section: Discussionmentioning
confidence: 99%
“…, Leitao et al. ). The use of the power scaling relationship in this study was based on the following considerations: (1) our observations fit the power scaling relationship well (Appendix ); (2) as described earlier, the power scaling has been successfully adopted to scale many urban properties (Bettencourt et al.…”
Section: Methodsmentioning
confidence: 98%
“…We realized that the relationship between urban attributes can be analyzed using other methods such as direct comparison or statistic regression (Bloom et al 2008, Leitao et al 2016. The use of the power scaling relationship in this study was based on the following considerations:…”
Section: Horizontal Organization and Scaling Of Urban Attributes Acromentioning
confidence: 99%
“…where N s is the state population and β = 1.1397 is a scaling exponent independently estimated on the total volume of pageviews in each state by adopting the probabilistic framework of Leitão et al [59] (details are reported in the S2 Appendix of the Supporting Information). By K-fold (k = 10) and leave-one-out cross validation, we test the performance of the model considering different linear combinations of features X i .…”
Section: Equal-time Regression Modelmentioning
confidence: 99%